Navigating the Diagnostic Maze: A Case Report of Uncommon Cardiac Metastasis in Childhood Ewing Sarcoma - Narayanan, Balaji; Sharma, Jitendra; Ahuja, Meenakshi; Kamalesh, Raghavendra; Khurana, Ujjawal; Malik, Rajesh (Indian Journal of Medical and Paediatric Oncology, 2024)
Ewing sarcoma is a bone cancer affecting children and young adult males. It usually presents as a single bone tumor, but it can also occur in multiple locations. Nevertheless, Ewing sarcoma is an extremely aggressive tumor capable of metastasizing to other parts of the body, such as the lungs, bones, liver, and lymph nodes. Cardiac metastases are rare, indicating a poor prognosis, as they suggest that the cancer has become more advanced and challenging to treat.This case report describes a 9-year-old boy who presented with complaints of fever and multiple swellings in the calvaria, periorbital region, clavicle, and left thigh. Laboratory investigations revealed a high erythrocyte sedimentation rate, elevated absolute neutrophil count, high phosphate and calcium levels, and low magnesium levels. Computed tomography imaging revealed the presence of multifocal osseous expansile lytic lesions, multiple pulmonary metastases, and extensive soft tissue involvement of the heart. Based on these findings, possible differential diagnoses of Langerhans cell histiocytosis, lymphoma, and Ewing sarcoma were considered. Further histopathological examination and immunohistochemistry confirmed a final diagnosis of metastatic Ewing sarcoma.The most common metastasis sites for Ewing sarcoma are the lungs, with rare occurrences in the central nervous system, and metastasis to the heart is uncommon. We present here a rare undiagnosed Ewing sarcoma with cardiac metastasis, in addition to pulmonary and multifocal osseous metastasis. This case is unique because multifocal osseous involvement is rare and further lung and heart involvement is even rarer in Ewing sarcoma.
Keywords: Ewing sarcoma; multifocal osseous metastasis; lung metastasis; cardiac metastasis; case report